Use of Veterinary Vaccines for Livestock as a Strategy to Control Foodborne Parasitic Diseases - Sander, Valeria A.; Sánchez López, Edwin F.; Mendoza Morales, Luisa; Ramos Duarte, Victor A.; Corigliano, Mariana G.; Clemente, Marina (Frontiers in Cellular and Infection Microbiology, 2020)
Foodborne diseases (FBDs) are a major concern worldwide since they are associated with high mortality and morbidity in the human population. Among the causative agents of FBDs, Taenia solium, Echinococcus granulosus, Toxoplasma gondii, Cryptosporidium spp. and Trichinella spiralis are listed in the top global risk ranking of foodborne parasites. One common feature between them is that they affect domestic livestock, encompassing an enormous risk to global food production and human health from farm to fork, infecting animals and people either directly or indirectly. Several approaches have been employed to control FBDs caused by parasites, including veterinary vaccines for livestock. Veterinary vaccines against foodborne parasites not only improve the animal health by controlling animal infections but also contribute to increase public health by controlling an important source of FBDs. In the present review, we discuss the advances in the development of veterinary vaccines for domestic livestock as a strategy to control foodborne parasitic diseases.